Relationship between waste disposal and public satisfaction in local authorities in Kedah - Zakaria, Zaherawati; Noordin, Nazni; Yaacob, Mahazril 'Aini; Ngah, Kamaruddin; Mohamed Sawal, Mohd Zool Hilmie; Mustaffa, Jamaludin (Canadian Academy of Oriental and Occidental Culture, 2011)
This paper is explains the relationships between waste disposaland customer satisfaction in local government functions. Due to public complaints rising in waste disposal andcleanliness and poor services given by the local authoritiesnowadays lead to this study. The primary objective ofthis study is to investigate the customer’s satisfactionon waste management provided by local government inKedah. Instead of that, the study also aims at examiningthe relationship between independent variables withpublic perception towards services provided by thecouncil. This study used Descriptive Statistic and Pearson Correlation for data analysis on hypotheses which issignificant relationships in findings Recommendations were propose to increase better performance by its councils. In future research, local authorities should bemore active collaboration with the focus groups including business communities and public at large in boost up the performance in its services.